Evolution Of Views on State Management in Farabi's Work "The City of Virtuous People". - Muxiddin Karimberdiyev (Genius Publishing Group, 2023)
In this article, Farobi's theories on statehood and management are given
Keywords: Government; eloquence; wisdom